KONDISI KUALITAS AIR (ASPEK MIKROORGANISME) DI PERAIRAN SEKITAR PULAU BUNAKEN, SULAWESI UTARA - Roberto V Larat; Markus T Lasut; Robert A Bara (Sam Ratulangi University, 2017)
In general, water conditions surrounding Bunaken Island are not separated from the liquid waste disposal, for example: bathing, washing, latrines, and landfills. Based on this, the research was conducted to determine the content of microorganisms Escherichia coli and coliform derived from liquid waste around Bunaken Island. The result showed the concentrations of E. coli were point (TS) I (<1 MPN / 100 ml), II (<1 MPN / 100 ml), and III (<1 MPN / 100 ml), and at the sampling point (TS) IV (1.0 MPN / 100 ml), V (1.0 MPN / 100 ml), and VI (1.0 MPN / 100 ml). Furthermore, coliform concentration has the similar valueat each sampling points (TS) I, II, III, IV, V, and VI with the amount of 2.0 MPN / 100 ml. The status around the Bunaken island on the comparison table between the this results and the standards of the Sea Quality Standard for Marine Tourism still qualifies or does not exceed the limits which stated in the creed of Minister ofEnviromental Affair Republic of Indonesia number 179 of 2004. Followed by Creed of Minister ofEnviromental Affair number 51 of 2004 on the Quality of Raw Water for Marine Biota, is categorized as the